Beyond Endorsement: How Customer Equity Shapes the Celebrity Endorsement–Loyalty Link in Nigeria’s Telecom Sector - Onamusi, Abiodun B.; Anafi, Olanrewaju I.; Trihudiyatmanto, M. (NIU Journal of Management Sciences, 2026)
Customer loyalty remains a persistent strategic challenge in Nigeria’s telecommunications industry, where intense competition and low switching costs undermine long-term profitability and sustainability. This raises critical questions regarding whether celebrity endorsement alone is sufficient to cultivate durable loyalty and whether customer equity strengthens this relationship. Anchored on Source Credibility Theory and the Customer Equity Framework, this study examines the moderating effect of customer equity on the relationship between celebrity endorsement and customer loyalty among telecom subscribers in Lagos State, Nigeria. Adopting a positivist research paradigm, primary data were collected from 432 mobile subscribers using a validated structured survey instrument. The data were analyzed using moderation regression analysis. The results indicate that customer equity significantly enhances the effect of celebrity endorsement on customer loyalty, with a statistically significant change in explained variance (ΔR² = 0.015; F = 15.547; p < 0.001). The findings suggest that customer perceptions of brand value, trust, and relational strength amplify the effectiveness of celebrity endorsement strategies. The study implies that telecommunications firms seeking to strengthen customer loyalty should complement celebrity endorsement campaigns with deliberate investments in customer equity-building mechanisms such as trust enhancement, value delivery, and long-term relational engagement. Keywords: Customer equity, brand equity, relationship equity, celebrity endorsement, telecom sector, Lagos.